The Gac/Rsm and cyclic‐di‐GMP signalling networks coordinately regulate iron uptake in Pseudomonas aeruginosa. (25th June 2013) - Frangipani, Emanuela; Visaggio, Daniela; Heeb, Stephan; Kaever, Volkhard; Cámara, Miguel; Visca, Paolo; Imperi, Francesco
Summary Pseudomonas aeruginosa is a versatile bacterial pathogen capable of occupying diverse ecological niches. To cope with iron limitation, P. aeruginosa secretes two siderophores, pyoverdine and pyochelin, whose ability to deliver iron to the cell is crucial for biofilm formation and pathogenicity. In this study, we describe a link between iron uptake and the Gac/Rsm system, a conserved signal transducing pathway of P. aeruginosa that controls the production of extracellular products and virulence factors, as well as the switch from planktonic to biofilm lifestyle. We have observed that pyoverdine and pyochelin production in P. aeruginosa is strongly dependent on the activation state of the Gac/Rsm pathway, which controls siderophore regulatory and biosynthetic genes at the transcriptional level, in a manner that does not involve regulation of ferric uptake regulator (Fur) expression. Gac/Rsm‐mediated regulation of iron uptake genes appears to be conserved in different P. aeruginosa strains. Further experiments led to propose that the Gac/Rsm system regulates siderophore production through modulation of the intracellular levels of the second messenger c‐di‐GMP, indicating that the c‐di‐GMP and the Gac/Rsm regulatory networks essential for biofilm formation can also coordinately control iron uptake in P. aeruginosa.